Effect of a ß-Mannanase on Nutrient Digestibility in Corn-Soybean Meal Diets for Broiler Chicks - Mussini, F.J.; Coto, C.A.; Goodgame, S.D.; Lu, C.; Karimi, A.J.; Lee, J.H.; Waldroup , P.W. (International Journal of Poultry Science, 2011)
The possibility of improving digestibility of nonstarch polysaccharides present in broiler diets by the use of different carbohydrase enzymes appears as an opportunity to enhance feed utilization by the birds. In this study, the effect of a beta-mannanase product on nutrient digestibility in corn-soybean meal diets was investigated. One-day-old chicks received a nutritionally complete corn-soybean meal for 19 days. At that time birds were randomly allocated to four treatments, each of which had six replicates of five birds housed in battery brooders with wire floors. Aliquots of the basal diet were supplemented with four levels of CTCZYME (CTC Bio Inc., Seoul Korea): 0%, 0.025%, 0.05% (recommended level) and 0.10%. Chromic oxide was used as an indigestible marker. Feed was analyzed for gross energy, chromium and amino acid content. After eight days of acclimation to the test diets, birds were sacrificed and ileal contents collected. Analysis of the ileal contents indicated that digestibility of Lys, Met, Thr, Trp, Arg, Leu, Ile, Cys and Val were significantly (p<0.0001) improved in a linear manner for each increment of enzyme. Ileal apparent metabolizable energy increased with each increment of CTCZYME level. These results show that the enzyme improves feed digestibility by making amino acids more available for the bird and increases energy utilization from the feed. These results suggest that lower levels of protein and energy could be used with the same results but further studies are required to estimate potential levels.